S3 Idiopathic Pulmonary Fibrosis, Mesothelioma, And Asbestosis Mortality Trends For England And Wales: Is Asbestos Exposure Associated With Ipf?. (10th November 2014) - Reynolds, C; Barber, C; Cullinan, P
Abstract : Introduction and objectives: Idiopathic pulmonary fibrosis (IPF) is more common in older people, in men, in manual workers, and in those living in more industrial areas of the country. It has been hypothesised that workplace asbestos exposure is an under-recognised cause of IPF. Studies of mesothelioma patients have shown that asbestos exposure is poorly recalled. If asbestos exposure is not known, asbestosis can be misclassified clinically as IPF because both can present with progressive breathlessness and radiological UIP. Our aim was to investigate a possible association between IPF and known asbestos-related mortality. Our objective was to visualise age-standardised annual mortality trends for IPF, mesothelioma, and asbestosis for men and women. Methods: Age, sex, and region stratified mortality data for IPF, mesothelioma, and asbestosis were obtained for England and Wales from the Office of National Statistics for the period 1974–2012. Data were age-standardised and visualised using the Python Pandas data analysis library and matplotlib. Results: The incidence of IPF continues to increase and is higher in men (male:female = 1:1.6) and in the north west of England. IPF and asbestos-related deaths are rare before the age of 40 and more common in elderly people. Conclusions: New antifibrotic treatments for IPF throw into sharp focus the question of whether or not a proportion of IPF is due to occult asbestos exposure; patients known to have asbestos exposure are currently not considered to be candidates for antifibrotic treatments. Our data are consistent with a proportion of IPF being attributable to asbestos exposure but are not conclusive and further research is needed.